Institutional strategies implementing outcome-based education for engineering - first experiences from Universiti Teknologi Malaysia - Mohammad, Shahrin; Tapsir, Siti Hamisah; Idris, Ahmad Kamal; Kamsah, Mohd. Zaki; Abu, Mohd. Salleh; Abu Hassan, Norihan (Loughborough: Higher Education Academy Engineering Subject Centre and the UK Centre for Materials Education, 2008)
Being a developing nation, Malaysia strives to compete within the global frontiers in science and technology. Compared with developed nations, educating and training of engineers is viewed as social needs and obligations. Over the last fifty years of independence, there has been a mushrooming of industries, resulting in a high demand for engineers. The expectation to produce quality engineers is high, and this role is not an easy task. Universiti Teknologi Malaysia (UTM) has been responsible for producing the majority of engineers for the country for more than 30 years. With the impact of the Engineering Criteria 2000 (EC2000), crafted by ABET, the university has been continuously stepping up efforts to improve its programmes to meet the above aspirations. Therefore, as Malaysias premier university for engineering, UTM first embarked on the development and implementation of a model of Outcome-Based Education (OBE) from as early as 2002 to programmes offered in the university. During that year, an awareness program regarding OBE was introduced to academic staff of the Faculty of Science. OBE was deemed essential to meet the requirement for Malaysia to become a full signatory member of The Washington Accord. The objectives of OBE are to incorporate professional skills into the programme curriculum, as well as knowledge and technical competencies of students. UTMs Outcome-Based Education has involved three stages of development: (i) the planning stage (ii) the implementation stage, and (iii) the assessment stage. Discussion in this paper focuses on the process of implementation, and the challenges faced by university administrators to make OBE successful.